A case of anemia caused by combined vitamin B12 and iron deficiency manifesting as short stature and delayed puberty - Seung Min Song; Keun Wook Bae; Hoi-Soo Yoon; Ho Joon Im; Jong-Jin Seo (Korean Pediatric Society, 2010)
Anemia caused by vitamin B12 deficiency resulting from inadequate dietary intake is rare in children in the modern era because of improvements in nutritional status. However, such anemia can be caused by decreased ingestion or impaired absorption and/or utilization of vitamin B12. We report the case of an 18-year-old man with short stature, prepubertal sexual maturation, exertional dyspnea, and severe anemia with a hemoglobin level of 3.3 g/dL. He had a history of small bowel resection from 50 cm below the Treitz ligament to 5 cm above the ileocecal valve necessitated by midgut volvulus in the neonatal period. Laboratory tests showed deficiencies of both vitamin B12 and iron. A bone marrow examination revealed dyserythropoiesis and low levels of hemosiderin particles, and a cytogenetic study disclosed a normal karyotype. After treatment with parenteral vitamin B12 and elemental iron, both anemia and growth showed gradual improvement. This is a rare case that presented with short stature and delayed puberty caused by nutritional deficiency anemia in Korea.